NITAZOXANIDE IN TREATMENT OF ROTAVIRUS DIARRHEA IN CHILDREN: A SINGLE CENTER STUDY - Aneeqa Adnan; Abdul Ahad Jamshaid; Muhammad Azhar Farooq; Tehreem Fatima (Journal of University Medical & Dental College, 2021)
BACKGROUND & OBJECTIVE: As Rota virus leads to significant morbidity in children 2 months to 5 years, this study was done to observe the effect of one dose of nitazoxanide on the total duration of rotavirus diarrhea. The primary objective was to evaluate the reduction in the mean duration of viral diarrhea in children after administration of first dose of Nitazoxanide. METHODLOGY: This descriptive study was done in the Department of Pediatric Medicine Unit I, Mayo Hospital, Lahore from Jan 2016 to June 2016 after approval from the ethical review committee. Sample size calculated was 175 using WHO sample size calculator. Patients of 4–5 years were given 200 mg nitazoxanide twice daily for 3 days; 100 mg nitazoxanide was given twice daily to 12–47 months age group, and patient of <12 months age were given 7.5 mg/kg twice day along with routine care and were followed 12 hourly till the passage of normally formed stools. Duration of diarrhea was recorded. RESULTS: Out of 175 cases, 58.9% (n=103) were between 2-36 months age while 41.2% (n=72) were 37-60 months age, mean+SD was calculated as 35.06+13.34 months, mean reduction in duration of rotavirus diarrhea in children after administration of first dose of Nitazoxanide was recorded as 32.85+2.32 hours. CONCLUSION: With the use of nitazoxanide along with routine care for rotavirus diarrhea children, the mean duration of rotavirus diarrhea was reported to be less than 1.5 days.